PKWT or Modern Slavery?: Exploring The Legal Consequences of Abuse of Contract Worker Status - Ahmad Fauzan; Nur Mohamad Kasim; Weny Almoravid Dungga (Universitas Internasional Batam, 2025)
This study discusses the misuse of the status of Fixed-Term Employment Agreements (PKWT) in the Indonesian employment system and its legal implications for worker protection within the framework of the Pancasila rule of law. The enactment of Law Number 11 of 2020 concerning Job Creation and its implementing regulations amended the limitative provisions of Article 59 of Law Number 13 of 2003 concerning Manpower, which originally provided legal certainty through time limits and an automatic conversion mechanism from PKWT to PKWTT. These changes create legal uncertainty, weaken protection for contract workers, and create potential violations of citizens' constitutional rights to decent work and livelihoods as guaranteed by Article 27 paragraph (2) of the 1945 Constitution. This study uses normative legal methods with a statutory and conceptual approach to examine the effectiveness of legal norms and their implementation practices in the field. The analysis shows that the misuse of PKWT has made employment relationships an instrument of exploitation, not protection, thus contradicting just and civilized humanitarian values. From the perspective of a Pancasila-based state based on the rule of law, the law should serve as a protector of vulnerable groups and ensure a balance between legal certainty, justice, and expediency. Therefore, a reconstruction of employment policy is needed that reaffirms the law's function as an instrument of social justice by strengthening oversight mechanisms, sanctions, and ensuring the status of contract workers in Indonesia.